Database Screening of Ternary Chalcogenides for P-type Transparent Conductors - Raghupathy, Ramya Kormath Madam; Wiebeler, Hendrik; Kühne, Thomas D.; Felser, Claudia; Mirhosseini, Hossein (Chemistry of Materials, 2018)
In this work, we investigated ternary chalcogenide semiconductors to identify promising p-type transparent conducting materials (TCMs). High-throughput calculations were employed to find the compounds that satisfies our screening criteria. Our screening strategy was based on the size of band gaps, the values of hole effective masses, and p-type dopability. Our search led to the identification of seven promising compounds (IrSbS, Ba2GeSe4, Ba2SiSe4, Ba(BSe3)2, VCu3S4, NbCu3Se4, and CuBS2) as potential TCM candidates. In addition, branch point energy and optical absorption spectra calculations support our findings. Our results open a new direction for the design and development of p-type TCMs.
CRIS-Team Scopus Importer:2022-04-14